2013
DOI: 10.1097/rhu.0b013e318289bd16
|View full text |Cite
|
Sign up to set email alerts
|

Current Daily Glucocorticoid Use and Serum Creatinine Levels Are Associated With Lower 25(OH) Vitamin D Levels in Thai Patients With Systemic Lupus Erythematosus

Abstract: Vitamin D deficiency and insufficiency are common in SLE patients despite more than half of them taking vitamin D supplementations. Higher serum creatinine level and higher current daily glucocorticoid dose are associated with lower serum 25(OH) vitamin D levels. These patients may require higher doses of vitamin D supplementations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 34 publications
3
35
0
1
Order By: Relevance
“…It is possible that NMOSD patients with higher levels of disability showed lower 25(OH)D 3 levels because lifestyle changes led to less outdoor activity and inadequate sun exposure after the disease onset. In addition, daily oral glucocorticoid use during the disease course may be associated with lower 25(OH) vitamin D levels, as observed in SLE patients [28]. However, our results demonstrated that vitamin D levels were higher in patients with longer disease duration.…”
Section: Discussionsupporting
confidence: 44%
“…It is possible that NMOSD patients with higher levels of disability showed lower 25(OH)D 3 levels because lifestyle changes led to less outdoor activity and inadequate sun exposure after the disease onset. In addition, daily oral glucocorticoid use during the disease course may be associated with lower 25(OH) vitamin D levels, as observed in SLE patients [28]. However, our results demonstrated that vitamin D levels were higher in patients with longer disease duration.…”
Section: Discussionsupporting
confidence: 44%
“…GC and CsA treatments may lead to fluctuations in the vitamin D level in SLE patients. GC exposure has been reported to be associated with high [12], equivocal [13], or low [14,36] vitamin D levels. An animal study revealed that CsA treatment is associated with vitamin D resistance through downregulation of vitamin D receptors in spite of an increase in 1,25(OH) 2 D 3 level [37].…”
Section: Fgf-23 Bone Metabolism and Fgf-23 Determinantsmentioning
confidence: 99%
“…Elevated FGF-23 is associated with increased overall osteoporotic fracture risk in elderly men [11]. The relationships among GC treatment, BMD, PTH, and vitamin D level in SLE patients have been elucidated in recent years [12][13][14][15]. However, the effects of GC and CsA treatment on bone metabolic profiles, especially the FGF-23 level, and their relationships to BMD in SLE patients have not been investigated, and the role of FGF-23 and other markers of bone metabolism in drug-induced osteoporosis are less described.…”
Section: Introductionmentioning
confidence: 99%
“…1 2 Studies within patients with SLE indicate that lower 25[OH]D levels may correlate with increased disease activity, [3][4][5][6][7][8][9][10][11][12][13][14][15][16] although inconsistently. [17][18][19][20][21][22][23][24] Variation within the vitamin D receptor gene (VDR), the vitamin D receptor protein that binds the active form of vitamin D, 1,25-dihydroxyvitamin D (1,25[OH] 2 D), has been associated with higher SLE disease activity in females 25 and higher damage score. 26 Whether vitamin D is related to risk of developing SLE has not been clearly established.…”
Section: Introductionmentioning
confidence: 99%